Zakat Management Model: A Systematic Literature Review - Annisa Maulidia Alfian; Muhammad Zilal Hamzah; Annisa Fitri (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
This research aims to explore the implementation of effective zakat management based on previous research and determine the methods used by previous research to analyze zakat management. This research uses qualitative methods with a systematic literature review approach. The process of this research consists of; formulating problems, developing and validating, reviewing Protocols, searching literature, screening articles that meet the inclusion criteria, assessing the quality of papers included in the inclusion category, and extracting data. Analyze and synthesize data and end with reporting of findings. In identifying journals that suit the required topic, this paper uses several keywords based on the research question, including synonyms for the main keyword. The electronic data source used is a primary literature search. Based on the research results, it can be concluded that to increase the effectiveness of zakat management, good human resources and governance are needed. Apart from that, technology adoption is also needed. Because, in this digital era, zakat management will become easier and more effective through the use of technology and the implementation of an integrated information system. In carrying out this, the quality of zakat managers must be improved so that they can carry out the digitalization process of zakat management.